Addressing the Digital Divide in Madrasah: Strategies for Improving Infrastructure and Educator Competence Towards Learning Transformation - Supriyanto (AMUYA: JOURNAL OF MANAGEMENT, 2026)
Digital transformation is inevitable for Islamic schools (madrasah) in responding to the demands of 21st-century competencies. However, the implementation of digital technology in Islamic educational institutions faces serious gaps marked by weak technology integration into core learning processes. This condition is caused by a combination of factors: inadequate ICT infrastructure, low educator digital competency, and stagnant technology utilization for administrative functions rather than pedagogical transformation. The Urgency, Seriousness, Growth (USG) analysis identified Low Educator Digital Competence as the top priority to be addressed (Score 15), followed by Technology Infrastructure (Score 14). The purpose of this policy article is to formulate a comprehensive intervention strategy to overcome these obstacles and encourage Islamic schools to achieve an optimal level of digital transformation. Methodology This writing uses a comprehensive desk research approach, referring to digital education theoretical frameworks such as TPACK and technology adoption models (e.g., SAMR) to analyze the root causes. Primary qualitative data was collected through a synthesis of recent research findings related to madrasah digitalization in Indonesia. Prioritization of issues is structured using the USG (Urgency, Seriousness, Growth) method based on existing data to determine the focus of policy recommendations. The analysis shows that the key to addressing this problem lies in shifting the policy focus from simply procuring devices to strengthening human resources and pedagogy. Three main pillars of intervention are recommended: (1) Continuous improvement of educator competency in digital pedagogy; (2) Acceleration of stable ICT infrastructure equity; and (3) Change in the vision of technology utilization from administrative to transformative curriculum integration. The implementation of this strategy is expected to optimize ICT investment and make madrasahs competitive educational institutions.